Small-sided games versus continuous endurance training in female handball players - Belka, J.; Hulka, K.; Šafár, M. (Journal of Human Kinetics, 2023)
The main aim of the study was to compare the training methods of continuous endurance training versus handball small-sided games (SSGs) in female handball players during the preseason. Eighteen female handball players from a first league in the Czech Republic voluntarily participated in the study. They were divided into two groups (the SSG group [n = 9; age: 21.22 ± 3.03 years] and a running group (RG) [n = 9; age: 23.78 ± 3.77 years]). Both groups continued regular preseason training for six weeks. The SSG group played two small-sided games per week (a total of 12 games during the monitoring period) in their training sessions during the monitored six-week period. The RG ran twice per week, participating in continuous endurance training in the 12 training sessions during the monitored six-week period. Fitness tests (pretest/posttest) were performed prior to the six weeks of intervention and one week afterwards. The order of the fitness tests in sequence was as follows: 20-m and 30-m sprints, a Modified Agility T test (MAT), a Standing Long-Jump Test, ball-throwing velocity, and a Yo-Yo Intermittent Test level 1. In the SSG group, there was a significant improvement in the T test (p = 0.034), ball-throwing velocity (p = 0.019), and the Yo-Yo IR1 (p = 0.003) performance. The RG showed a significant improvement in the Standing Long-Jump Test (p = 0.049), ball-throwing velocity (p = 0.003), and the Yo-Yo IR1 (p = 0.003) performance. In conclusion, the SSGT method had a positive effect on female players` MAT, ball-throwing velocity and YoYo IR1 results, and the CERT method had a significant effect only on the YoYo IR1 results. Handball SSGs are a more suitable training method due to exercise specificity.